Research methodology : methods and techniques - Kothari, C.R.; Kothari, D. P. (Dwarkadas Pralhaddas), 1944- (Boca Raton : Chapman & Hall/CRC Press, 2019)
"The book Research Methodology: Techniques and Trends focuses on both undergraduate and post graduate courses; and it helps to understand the basic concepts and application of results directly to real life business, industry and research organization. Features: At the end of each chapter, to test conceptual understanding of the subject and put theory into practice, review questions are included, which would help in understanding of key concepts and ideas. The book contains in-depth coverage of concepts and techniques. Throughout the text, tables and figures are presented to illustrate the concepts and techniques. This book gives students essential guidance on how to carry out their own research projects. The book covers a wide range of research methods, approaches to research, and ways of carrying out analysis of data. It is a textbook on research methodology for the doctoral and post-doctoral programs, post graduate courses such as MSc, MBA, MCA, MS, etc., to name a few. Though the book is primarily addressed to students, it will be equally useful to researchers and entrepreneurs as well"--
Includes bibliographical references and index.
Keywords: Research -- Methodology